Combination Therapy Life Review Therapy and Emotional Freedom Technique Therapy (LR-EFTT) for Depression on Chemotherapy Elderly - Alwi, Nike Puspita (Jurnal Kesehatan - STIKes Prima Nusantara, 2024)
Background: Being old and experiencing chemotherapy can have a negative effect on mental well-being, causing expanded uneasiness and discouragement. Researchers have investigated various therapies as potential arrangements to address these mental challenges. Some studies showed that monotherapy utilizing either life review therapy or emotional freedom technique therapy is successful in lightening discouragement. Purpose: To explore the effectiveness of combining life review therapy and emotional freedom technique therapy to ease or decrease the depression of an elderly person who took chemotherapy. Methods: The design of our study was a quasi-experiment on an elderly person who took a chemotherapy regimen at Achmad Moechtar Bukittinggi District Hospital in Bukittinggi. We used accidental sampling and a sample size of 20 respondents. A total of six sessions of LR-EFTT, a combination therapy of life review therapy and emotional freedom technique therapy, were given to 10 people who met the criteria and were in the intervention group. Ten people who were in the control group did not receive any intervention. Data was collected by using the Geriatric Depression Scale-15 in order to assess the dependent variable, which met the validity and reliability (Cronbach α = 0.817), and use an independent t-test to conclude this research. Results: We found that there was a significant difference in depression between the two groups (p-value = 0.000). The mean of the control group (10.1) is higher than the intervention group (6.20). Conclusion: It concludes that combined therapy of life review therapy and emotional freedom technique therapy (LR-EFTT) was effective in reducing depression in elderly patients undergoing chemotherapy